logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  JEEMAIN and AIPMT  >>  Mathematics  >>  Trignometry
0 votes

The value of $\cot\sum\limits_{n=1}^{23}\cot^{-1}\big(1+\sum\limits_{k=1}^n 2k\big)$ is

$(a)\;\large\frac{23}{25}$$\qquad(b)\;\large\frac{25}{23}$$\qquad(c)\;\large\frac{23}{24}\qquad$$(d)\;\large\frac{24}{23}$

Can you answer this question?
 
 

1 Answer

0 votes
$\cot^{-1}\big(1+\sum\limits_{k=1}^n2k\big)=\cot^{-1}[1+n(n+1)]$
$\qquad\qquad\qquad\quad=\tan^{-1}\big[\large\frac{(n+1)-n}{1+(n+1)n}\big]$
$\qquad\qquad\qquad\quad=\tan^{-1}(n+1)-\tan^{-1}n$
$\therefore \sum\limits_{n=1}^{23}[\tan^{-1}(n+1)-\tan^{-1}n]=\tan^{-1}24-\tan^{-1}1$
$\qquad\qquad\qquad\qquad\qquad\quad\;\;=\tan^{-1}\large\frac{23}{25}$
$\therefore \cot\big[\sum\limits_{n=1}^{23}\cot^{-1}\big(1+\sum\limits_{k=1}^n 2k\big)\big]=\cot^{-1}\big[\tan^{-1}\large\frac{23}{25}\big]$
$\Rightarrow \large\frac{25}{23}$
Hence (b) is the correct answer.
answered Oct 16, 2013 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...